2022
DOI: 10.3390/nursrep12040089
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Habits of Latvian Nursing Students: A Cross-Sectional Study

Abstract: It is important to integrate knowledge about the need for physical activities (PA) in the prevention and care of human health in nursing study programs so that nurses can promote PA among their patients. This study aims to evaluate the PA habits of Latvian nursing students. Participants were students of three universities in Latvia who were enrolled in a four-year bachelor study program, “Nursing”, with a total of 341 after the data cleaning (population size n = 1554). The questionnaire contained questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Nursing students are also cited to be physically inactive [21,22]. In a study of 264 nursing students, 68.6% of the students were not meeting the recommended amounts of PA [23]. A study conducted focus groups with Australian nursing students and identified individual (e.g., lack of motivation, lack of knowledge), environmental (e.g., time, finances, limited access to PA resources), and psychosocial (e.g., competing priorities, increased cognitive load, lack of social interaction and support) barriers to PA [22].…”
Section: Barriers To Physical Activity In Nursingmentioning
confidence: 99%
“…Nursing students are also cited to be physically inactive [21,22]. In a study of 264 nursing students, 68.6% of the students were not meeting the recommended amounts of PA [23]. A study conducted focus groups with Australian nursing students and identified individual (e.g., lack of motivation, lack of knowledge), environmental (e.g., time, finances, limited access to PA resources), and psychosocial (e.g., competing priorities, increased cognitive load, lack of social interaction and support) barriers to PA [22].…”
Section: Barriers To Physical Activity In Nursingmentioning
confidence: 99%